HUBUNGAN ANTARA GANGGUAN POLA TIDUR PADA IBU NIFAS DENGAN KEJADIAN POSTPARTUM BLUES DI WILAYAH KERJA PUSKESMAS PEMBANTU SIDOHARJO KECAMATAN GEDEG KABUPATEN MOJOKERTO - Khusniyati, Etik; Yuli Astuti, Fitria (Jurnal Keperawatan Bina Sehat, 2010)
Accomplishment of requirement sleep and rest is vital importance for mother afterbirth so that earning quicker repair damage at cell. Mother which have borne will experience of change of physical and psychological which caused by trauma at inpartu, the mentioned make pattern sleep mother not regular, wit main problem in the form of sleep cycle which by snatches so that can cause less sleep. Rest and less sleep at mother afterbirth will influence several things, among others cause depresi, going concern depresi will cause the happening of postpartum blues so that cause mother incapable of taking care of their self and baby.This research is to know relation between pattern trouble sleep at mother afterbirth with occurrence of postpartum blues in region work ministrant puskesmas Sidoharjo District of Gedeg Sub-Province Mojokerto. This type research is analytic by using approach of cross sectional, in this research its population that is all mother afterbirth exist in region work ministrant puskesmas sidoharjo district of sub-province gedeg of mojokerto counted 43 people, this research use sampling technique of purposive sampling where its him is mother afterbirth in region work ministrant puskesmas sidoharjo district of gedeg sub-province mojokero fulfilling criterion of inklusi, that is counted 16 people. Take the data by interview and observation by using data collecting appliance in the form of sheet interview and checklist, gathered data is later analysed by deskriptif, to know the existence of relation assisted with hypothesis test by using test of Fisher test exact probability. Result of hypothesis test of fisher test exact probability got by value of P equal to 0,001 smaller than = 0,05, hence Ho refused, this matter indicate that there is relation between pattern trouble sleep at mother afterbirth with occurrence of postpartum blues in region work ministrant puskesmas sidoharjo district of gedeg sub-province mojokerto.Result of hypothesis test of Fisher test exact probability got by value of P equal to 0,001 smaller than = 0,05, hence Ho refused, this matter indicate that there is relation between pattern trouble sleep at mother afterbirth with occurence of blues postpartum in region work ministrant puskesmas sidoharjo district of gedeg sub-province mojokerto. Referring to result of research, midwife can give input about way of handling sleep pattern trouble, with sleep and rest which enough and time benefit as well as possible so that mother can rest so that requirement of his sleep earn fulfilled and in the end can prevent blues postpartum and cure energy.Keyword: Postpartum blues